Pemberdayaan Anggota PKK melalui Pelatihan Pembuatan Lilin Aromaterapi untuk Meminimalisir Limbah Minyak Jelantah - Kafitri, Muhammad Khairul; Sari, Indah Novita; Sari, Vivi Aullia (Muria Jurnal Layanan Masyarakat, 2024)
Minyak Jelantah, used cooking oil that is used repeatedly, has bad impacts on health and the environment. This program aims to increase public awareness of the dangers of using Minyak Jelantah (used cooking oil) and provide skills in making aromatherapy candles. This program involves planning, education, simulation, and evaluation stages. Training participants, specifically Family Welfare and Empowerment Organization (Pemberdayaan Kesejahteraan Keluarga) women from Tergo Village, were given education about the benefits of aromatherapy candles and practical skills in making candles. The results showed an increase in participants' knowledge about the dangers of Minyak Jelantah (used cooking oil) and the benefits of aromatherapy candles. The process of making aromatherapy candles is simple and economical, using ingredients that are easy to find. This program has succeeded in increasing environmental awareness and providing an economical alternative to the use of Minyak Jelantah (used cooking oil). This program is advantageous in reducing environmental pollution and increasing public understanding of health.